2015
DOI: 10.1186/s12937-015-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary patterns with serum adipokines among Japanese: a cross-sectional study

Abstract: BackgroundDiet may influence disease risk by modulating adipokines. Although some foods and nutrients have been linked to circulating adipokine levels, little is known about the role of dietary patterns on adipokines. We investigated the association between major dietary patterns and circulating levels of adiponectin, leptin, resistin, visfatin, and plasminogen activator inhibitor-1 (PAI-1) in a working population.MethodsThe subjects were 509 employees (296 men and 213 women), aged 20 to 65 years, of two munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
3
25
1
2
Order By: Relevance
“…In a hospital-based case-control study for type 2 diabetes in Kumasi (diabetes cases, 538; controls, 668. According to Kashino et al (2015) diet have been identified as one of the modifiable factors that may affect adipokines such as adiponectin and leptin which are the important biochemical indices that might have a role in health and disease. Hence, it is important to see the association of adiponectin and leptin concentration with different types of dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a hospital-based case-control study for type 2 diabetes in Kumasi (diabetes cases, 538; controls, 668. According to Kashino et al (2015) diet have been identified as one of the modifiable factors that may affect adipokines such as adiponectin and leptin which are the important biochemical indices that might have a role in health and disease. Hence, it is important to see the association of adiponectin and leptin concentration with different types of dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, adiponectin, visfatin and tumour necrosis factor-α are among a wide range of adipokines that responsible for majority of endocrine, metabolic and vascular disorder related to obesity and obesity mediated adverse effects on glucose and lipid metabolism (JafariVayghan et al 2015;Monzillo et al 2003)adiponectin, resistin, tumor necrosis factor-alpha (TNF-alpha. Leptin concentration has been associated with a higher risk of type 2 diabetes, hypertension and chronic heart disease (Kashino et al 2015). According to Jafari-Vayghan et al (2015) the role in the regulation of food intake and energy expenditure is exerted by the leptin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary components may modulate the risk of diseases by altering the levels of adipokines secretion and/or sensitivity [33,44,45]. In this study of Jordanian adults, we highlighted a few associations between dietary consumption of macro-and micro-nutrients and serum levels of leptin, adiponectin, IL-6, resistin, as well as leptin/adiponectin ratio.…”
Section: Discussionmentioning
confidence: 86%
“…Some of these nutrients includeomega-3 fatty acid [21,22], protein [23], sucrose [24], and dietary [22,25], or foods such as vegetables and fruits [26], whole grain [27], fish [28,29], and legumes [30]. However, other studies showed no association between some dietary component [s] such as vitamins and minerals with adipokine levels [31][32][33]. Studies examined the effect of dietary intake of vitamins and minerals on serum Background and Aim: Findings related to nutrient intakes and levels of adipokines concentrations are inconclusive.…”
Section: Introductionmentioning
confidence: 99%